2017
DOI: 10.15406/apar.2017.06.00210
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Biofortification of Iron and Zinc in Edible Portion of Crops for the Global South

Abstract: Iron (Fe) and zinc (Zn) are essential micronutrient for both human and plants, but Fe and Zn deficiency is prevalent in the world especially developing countries including India and China. Biofortification is considered the most promising approach to alleviate Fe and Zn malnutrition in developing countries. While agricultural approaches are also useful to gain Fe and Zn enriched cereals. Therefore, agro-biofortification of Fe and Zn by agricultural approaches was reviewed for possible solution in intensive agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several agrobiodiversity-related studies have focused on improving diets or dietary quality, including intake of key nutrients, dietary diversity, and consumption of micronutrientrich foods (e.g., Powell et al, 2015;Herrero et al, 2017). From the nutritional perspective, Fe and Zn are essential micronutrients for both humans and plants, but they remain deficient in the diets of the global population (Li et al, 2017). As reported in earlier studies (Ordóñez-Santos et al, 2011;Kapoulas et al, 2013;Mohammed et al, 2019), Fe is identified as a major micronutrient in the tomato fruit.…”
Section: Nutrient Concentrationmentioning
confidence: 99%
“…Several agrobiodiversity-related studies have focused on improving diets or dietary quality, including intake of key nutrients, dietary diversity, and consumption of micronutrientrich foods (e.g., Powell et al, 2015;Herrero et al, 2017). From the nutritional perspective, Fe and Zn are essential micronutrients for both humans and plants, but they remain deficient in the diets of the global population (Li et al, 2017). As reported in earlier studies (Ordóñez-Santos et al, 2011;Kapoulas et al, 2013;Mohammed et al, 2019), Fe is identified as a major micronutrient in the tomato fruit.…”
Section: Nutrient Concentrationmentioning
confidence: 99%